The immunohistochemical features of chorion and endometrium in women with early pregnancy losses. - Trohimovych, O. V. (Морфологія / Morphologia / Morfologìâ, 2015)
Background. According to present views proliferation and apoptosis plays an important role in the mechanisms of placenta formation, particularly in process of vasculogenesis that begins on the third week of pregnancy. Objective: To investigate the immunohistochemical features of chorion and endometrium in women with early pregnancy losses. Methods. 98 samples of abortive and surgical material in pregnant women in terms of 4-10 weeks of pregnancy were analyzed. 48 samples were obtained from women with missed abortion (1st group), 20 samples from women with spontaneous abortion (2nd group); 20 samples from women with tubal pregnancy (3rd group); 10 samples from pregnant women with normal singleton pregnancy, after medical abortion on their own wish (control group). Histological, histochemical and immunohistochemical methods were used. Monoclonal antibodies (MAbs) to Ki-67 and bcl-2 were applied. Results. Pathological picture of spontaneous abortion is characterized by the dominance of violation of blood circulation, presence of significant foci of hemorrhage occurring parallel with a pronounced disruption of apoptosis and proliferation in chorionic villi and decidual tissue, leading to the detachment of placenta. Conclusion. In 75% of cases of tubal pregnancy ectopic cytotrophoblast invasion is caused by prominent changes in the structure of the fallopian tube. First of all due to the inflammatory process and a sharp reduction of proliferation in the basal chorion and parietal deciduitis in 65% of cases.